PESTICIDES AS ENDOCRINE DISRUPTORS: IMPLICATIONS FOR FISH REPRODUCTION IN AQUATIC SYSTEMS (The Research of Medical Science Review, 2025)
This study examined the endocrine and reproductive effects of prolonged exposure to pesticide combinations in freshwater fish, using Clarias gariepinus as the test species conducted at University of Veterinary and Animal Sciences, Lahore, Pakistan. Fish were subjected to a 90-day exposure to environmentally relevant concentrations of a combination of chlorpyrifos, atrazine, and cypermethrin in a controlled laboratory setting. The treatment groups comprised a control, a low- and high-dose mixture, and a positive control subjected to 17α-ethinylestradiol. Critical physiological and molecular parameters were assessed, including the gonadosomatic index (GSI), plasma sex hormone concentrations (estradiol and testosterone), and induction of vitellogenin (VTon). Gene expression analysis and multivariate biomarker profiling were performed to evaluate the endocrine disruption signatures. The findings indicated a substantial decrease in GSI among all exposed groups, with minimal levels observed in the positive control and high-dose mixture groups. Plasma estradiol and testosterone concentrations decreased in a dose-dependent manner, signifying disruption of endocrine control. VTG levels were significantly increased in pesticide-exposed fish, especially in males, indicating xenoestrogenic activity and feminization. Principal Component Analysis (PCA) revealed a clear grouping of the exposed groups, with high-dose and positive control treatments exhibiting overlapping patterns, indicating a commonality in disruption mechanisms. Statistical analysis validated that the effects were substantial and biologically relevant in the present study. The study found that even minimal sub-lethal levels of pesticide combinations can cause substantial hormonal disruptions and reproductive deficiencies in freshwater fish. These findings underscore the ecological concerns associated with agricultural runoff and the necessity for stricter pesticide regulations and comprehensive risk assessment methodologies. These findings underscore the importance of evaluating chemical combinations and chronic exposure scenarios in ecotoxicology, particularly for native species that possess ecological and economic significance.